2021
DOI: 10.3389/fevo.2021.654846
|View full text |Cite
|
Sign up to set email alerts
|

Diversity in the Development of the Neuromuscular System of Nemertean Larvae (Nemertea, Spiralia)

Abstract: In studies on the development of nervous systems and musculature, fluorescent labeling of neuroactive substances and filamentous actin (f-actin) of muscle cells and the subsequent analysis with confocal laser scanning microscopy (CLSM), has led to a broad comparative data set for the majority of the clades of the superphylum Spiralia. However, a number of clades remain understudied, which results in gaps in our knowledge that drastically hamper the formulation of broad-scale hypotheses on the evolutionary deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 88 publications
(133 reference statements)
1
6
0
Order By: Relevance
“…In Malacobdella , unique morphological characteristics, such as the presence of a terminal sucker and the loss of sensory organs (apical/cerebral organs), formed in postembryonic stages. This finding aligns with a recent comparative study on embryonic/postembryonic development in Nemertea, which suggests that most of the within-clade morphological diversity in the phylum has resulted from postembryonic development [ 53 ]. Molecular phylogenetic analyses have shown that Malacobdella is robustly nested within the Amphiporiina and forms a clade with the land-dwelling monostiliferans Geonemertes , although the relationship is not well supported.…”
Section: Discussionsupporting
confidence: 91%
“…In Malacobdella , unique morphological characteristics, such as the presence of a terminal sucker and the loss of sensory organs (apical/cerebral organs), formed in postembryonic stages. This finding aligns with a recent comparative study on embryonic/postembryonic development in Nemertea, which suggests that most of the within-clade morphological diversity in the phylum has resulted from postembryonic development [ 53 ]. Molecular phylogenetic analyses have shown that Malacobdella is robustly nested within the Amphiporiina and forms a clade with the land-dwelling monostiliferans Geonemertes , although the relationship is not well supported.…”
Section: Discussionsupporting
confidence: 91%
“…Currently, data on the development of the nervous system by means of immunohistochemistry against serotonin and FMRFamide combined with analysis by confocal laser scanning microscopy are available for a handful of species from all three high-ranking clades of Nemertea (Hay-Schmidt, 1990;Chernyshev and Magarlamov, 2010;Maslakova, 2010a;Hindinger et al, 2013;Hiebert and Maslakova, 2015;von Döhren, 2016bvon Döhren, , 2021. However, both antibodies have so far only been studied in two species, Lineus albocinctus (Heteronemertea) (Hindinger et al, 2013) and Carinina ochracea (Carinomiformes) (von Döhren, 2016b).…”
Section: Discussionmentioning
confidence: 99%
“…In the developing juvenile of Pilidiophora inside the pilidial envelope, the developing proboscis also displays 5HT-lir neurite processes (Hay-Schmidt, 1990;Maslakova, 2010a). A dorsal nerve that is present in the larvae of C. ochracea and Tubulanus polymorphus (Tubulaniformes), is absent from the larva of C. rufifrons, although it is present in adults (Beckers et al, 2013;von Döhren, 2016bvon Döhren, , 2021. In Carinoma species (Carinomiformes), the dorsal nerve is also present in adults but has not yet formed in the investigated larval stages (Beckers et al, 2013;von Döhren, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations